From Empire to Anthropocene : The Novel in Posthistorical Times - Joseph, Betty, 1963- (Book collections on Project MUSE., 2023)
"This book is an analysis of the inventiveness of contemporary fiction and of ways in which it engages our understanding of time in relation to globalization and environmental damage. The book convincingly dispels the notion that so-called global novels in English preclude the possibility of historical analysis and social collectivity"--